2004
DOI: 10.1177/000348940411300203
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Fiber Type Composition of Human Interarytenoid Muscle

Abstract: Intrinsic laryngeal muscle investigations, especially those of the interarytenoid (IA) muscle, have been primarily teleologically based. We determined IA muscle anatomy and histochemical and immunohistochemical classification of extrafusal and intrafusal (muscle spindle) fibers in 5 patients. Extrafusal fibers were oxidative type I and glycolytic types IIA and IIX. Intrafusal fibers of muscle spindles were identified by the presence of tonic and neonatal myosin. The results demonstrate that the IA muscle has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
6
29
0
9
Order By: Relevance
“…Expression of developmental MHC isoforms was approximately 0.3% in humans and macaques and 0.05% in rats. Similar limited expression of developmental MHC has been demonstrated in many head and neck muscles by PCR and IHC Sundman et al, 2004;Tellis et al, 2004]. Detection of developmental MHC in these muscles is expected to be below the detection threshold of silver-or Coomassiestained protein gels, consistent with the general observation that these isoforms are not identified by electrophoresis in adult muscle.…”
Section: Developmental and Unconventional Mhc Expressionsupporting
confidence: 70%
“…Expression of developmental MHC isoforms was approximately 0.3% in humans and macaques and 0.05% in rats. Similar limited expression of developmental MHC has been demonstrated in many head and neck muscles by PCR and IHC Sundman et al, 2004;Tellis et al, 2004]. Detection of developmental MHC in these muscles is expected to be below the detection threshold of silver-or Coomassiestained protein gels, consistent with the general observation that these isoforms are not identified by electrophoresis in adult muscle.…”
Section: Developmental and Unconventional Mhc Expressionsupporting
confidence: 70%
“…In conclusion, although other receptors may mediate laryngeal sensory feedback during vocalization, such as muscle spindles in the human interarytenoid muscle (28) and mechanoreceptors in the laryngeal mucosa (12), we speculate that the short-latency sternothyroid responses found here provide evidence that spindles in extrinsic laryngeal muscles might provide sensory feedback regarding changes in laryngeal height. Possibly the rapid changes in laryngeal height, which occur during pitch changes (14), could generate somatosensory feedback for laryngeal control during voice production.…”
Section: Discussionmentioning
confidence: 69%
“…The presence of muscle spindles in the intrinsic laryngeal muscles in humans is controversial (19,23). One report found muscle spindles in the interarytenoid (28), others reported spindles in the thyroarytenoid muscle (4,5,24), whereas a more recent study failed to confirm the presence of spindles in the thyroarytenoid muscle (8).…”
mentioning
confidence: 99%
“…In some studies, only the 3 major MyHC isoforms (MyHC-1, -2a and -2x) were found [Wu et al, 2000a;Li et al, 2004;Tellis et al, 2004]. Similarly, even the unloaded maximal shortening velocities (V o ) of laryngeal type 1, 2a and 2x fibres were found to be similar to those of the limb muscles [D'Antona et al, 2002;Sciote et al, 2002].…”
Section: Abbreviations Used In This Papermentioning
confidence: 99%